إمكانية تجهيز أقمشة الجينز للاستخدام في تصنيع جاكيت البدلة الرجالي كلاسيك - زلط، علي السيد Zalat, Ali Alsayed; عمر، رأفت حسن; محمد، أيمن محمد إبراهيم (جامعة المنصورة - كلية التربية النوعية, 2012)
يهدف البحث إلى دراسة الطرق المختلفة لتجهيز وصياغة خامات الجينز لتصنيع جاكت البدلة الكلاسيك. يمكن تحديد مشكلة البحث في مدى إمكانية تصنيع جاكت بدلة كلاسيك من خامات الجينز يناسب الطبقات ذات الدخول المتوسطة والمحدودة، ما مدى تقبل المجتمع لجاكت البدلة الكلاسيك الذي تم تصنيعه من خامات الجينز من حيث الخامة والسعر والتصميم؟ وكانت فروض البحث: 1. توجد علاقة دالة إحصائيا بين خامة الجينز المصنوعة من القطن 100% قبل تجهيزها وبعد تجهيزها حتى تتناسب ومواصفات تصنيع جاكت البدلة الرجالي الكلاسيك. 2. توجد علاقة دالة إحصائيا بين خامة الجينز المصنوعة من القطن المخلوط (قطن + بولي استر) الخام وبعد تجهيزه أو معالجته كيميائيا ليتناسب ومواصفات تصنيع جاكت البدلة الرجالي الكلاسيك. 3. توجد علاقة دالة إحصائيا بين خامة الجينز المصنوعة من القطن المخلوط (قطن + ليكرا) الخام وبعد تجهيزه ومعالجته كيميائيا ليتناسب ومواصفات تصنيع جاكت البدلة الرجالي الكلاسيك. 4. توجد علاقة دالة إحصائيا بين أسلوب التجهيز النهائي لإنتاج جاكت البدلة الرجالي الكلاسيك (قطن 100%- قطن مخلوط بولي استر- قطن مخلوط ليكرا) وقوة الشد والاستطالة للخامات محل الدراسة. 5. توجد علاقة دالة إحصائيا بين أسلوب التجهيز النهائي للأقمشة قبل تصنيع جاكت البدلة الرجالي الكلاسيك وبين مقاومة الأقمشة للتجعد. 6. توجد علاقة دالة إحصائيا بين أسلوب التجهيز النهائي للأقمشة المختلفة وبين نسبة الانكماش للأقمشة محل الدراسة حتى تتناسب ومواصفات تصنيع جاكت البدلة الرجالي الكلاسيك. وكان منهج البحث: المنهج التجريبي. نتائج البحث: من خلال التحليل الإحصائي لعمليات التجهيز المختلفة التي أجريت على أقمشة الجينز المختلفة (قطن 100%- مخلوط "قطن 65% + بولي استر 35%- ليكرا "قطن 98% + ليكرا 2%). وقد تم التوصل إلى أن أفضل عينات قماش جينز مجهز كالتالي: قماش مخلوط (قطن 65% + بولي استر 35%) مجهز إنزيم، مخلوط (قطن 65% + بولي استر 35%) مصبوغ: قطن 100% مجهز إنزيم + حجر، قطن 100% مجهز كسترة. واتضح أن أفضل تجهيز لتصنيع الجاكت الرجالي الكلاسيك من خامات الجينز هو مخلوط (قطن 65%+ بولي استر 35%) مصبوغ، ثم يليه قطن 100% مجهز كسترة، ثم مخلوط (قطن 65%+ بولي استر 35%) مجهز إنزيم، ثم قطن 100% مجهز إنزيم + حجر، وذلك حسب ترتيب السهولة في التصنيع الكمي (الإنتاج بكميات كبيرة).
The research aims to study different ways of processing and dyeing of raw materials for the manufacture of jeans classic suit jacket. Can identify the research problem Vymdi the possibility of manufacturing a suit jacket Classic of raw jeans fit classes to middle-income and limited, to what extent the community to accept the classic suit jacket, which was manufactured from raw materials in terms of raw jeans, price and design? The research hypotheses: 1. There is a relationship statistically significant between the severity of jeans made from 100% cotton processing before and after processing to fit specifications and manufacturing men's classic suit jacket. 2. There are statistically significant relationship between severity of jeans made from cotton blended (cotton + polyester) raw and after processing or chemically manipulated to suit the specifications and manufacture of classic men's suit jacket. 3. There is a relationship statistically significant between the severity of jeans made from cotton blended (cotton + lycra) raw and after processing and chemically manipulated to suit the specifications and manufacture of classic men's suit jacket. 4. There are statistically significant relationship between the style of the final processing for the production of classic men's suit jacket (100% cotton - cotton mixed with polyester - cotton mixed with Lycra) and the tensile strength and elongation of the materials under study. 5. There are statistically significant relationship between the style of the final processing of fabrics manufactured by the classic men's suit jacket and fabrics for wrinkle resistance. 6. There are statistically significant relationship between the style of the final processing of fabrics and different between the percentage of shrinkage of the fabrics under consideration to fit industry standards and men's classic suit jacket. The research method: the experimental method. Search Results: Through statistical analysis of the various processing operations performed on the jeans of different fabrics (cotton 100% - a mixture of "Cotton 65% + polyester 35%" - Lycra, "Cotton 98% + 2% Lycra"). Has been reached that the best samples of cloth Jeans equipped as follows: A mixture of cloth (cotton 65% + polyester 35%) is equipped with an enzyme, a mixture (65% cotton + polyester 35%) dyed, 100% cotton is equipped with enzyme + stone, 100% cotton fitted Ckstrp. It turned out that the best processing for the manufacture of the jacket Men's Classic of raw jeans is a mixture of (cotton 65% + polyester 35%) dyed, and then followed by a 100% cotton fitted Ckstrp, then a mixture of (cotton 65% + polyester 35%) is equipped with an enzyme, then cotton 100% equipped with enzyme + stone, in order to ease in manufacturing the quantitative (mass production).
Keywords: صناعة الملابس -- الملابس الجاهزة -- أقمشة الجينز -- الملابس الرجالية